Construction Methods and Their Impact on the Productivity of the Construction Projects Site (Iraq Case Study) - Malallah, Mohammed (Anbar Journal of Engineering Science, 2025)
This study aims to investigate the impact of various construction methods on labor productivity in Iraq, focusing on traditional, prefabricated steel structures, precast concrete, and mechanical or self-build construction techniques. The research employs a descriptive-analytical methodology, utilizing a structured survey distributed to 200 participants from different construction industry sectors, including engineers, contractors, and field workers. The survey examines key indicators of labor productivity, such as task completion speed, work quality, labor costs, safety, and project cost.The findings reveal significant differences in labor productivity across the construction methods. Traditional construction methods moderately impacted task completion speed and work quality but were less efficient in terms of cost reduction and safety. On the other hand, prefabricated and precast concrete methods demonstrated improvements in work quality, safety, and cost efficiency, although with some limitations regarding flexibility. Steel structures offered enhanced durability and faster construction times, while mechanical and self-build methods utilizing automation significantly reduced labor costs and accelerated the construction process.Based on these results, the study recommends incorporating modern construction methods, such as prefabricated and mechanical techniques, to improve overall productivity in the Iraqi construction sector. Additionally, it emphasizes the importance of training and adapting to these advanced methods to ensure long-term efficiency, safety, and cost-effectiveness in construction projects.